2020
DOI: 10.1252/jcej.19we181
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamic and Mass Transfer Correlation in a Microbubble Aerated Stirred Tank Reactor

Abstract: Many chemical and biocatalytic reactions are consuming gaseous species like oxygen, provided by the mass transfer across interfaces of multiphase contact apparatuses. For biocatalytic reactions a macroscopic aeration can lead to reduced enzyme activity by foaming and shear forces and for fast chemical reactions in multiphase ows, the mass transfer limitation is often the bottleneck for a process optimization. The present study investigates the use of bubbles with diameters less than 100 µm for aeration of a 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Consequently, the shrinking behavior as well as the bubble formation is depending on the surface tension. In a previous study, we reported a decrease of 15.5% in surface tensions of a buffer solution containing 67.8 mg/L BSA or GOx, compared with pure water (Matthes et al, 2020). This change applies to the underlying system.…”
Section: Resultsmentioning
confidence: 88%
See 4 more Smart Citations
“…Consequently, the shrinking behavior as well as the bubble formation is depending on the surface tension. In a previous study, we reported a decrease of 15.5% in surface tensions of a buffer solution containing 67.8 mg/L BSA or GOx, compared with pure water (Matthes et al, 2020). This change applies to the underlying system.…”
Section: Resultsmentioning
confidence: 88%
“…As reported in the literature, especially the pore size distribution is expected to affect the oxygen transfer rate through the generated bubbles size distribution (Kazakis, Mouza, & Paras, 2008b; Kulkarni & Joshi, 2005; Tsuge and Hibino, 1983). In previous investigations using the same microbubble aerators, no significant difference in the BSD between the SPG and sintered frit for gassing rates up to 0.067 vvm, generated in BSA containing sodium acetate buffer, is determined (Matthes et al, 2020). The 5 mm (single hole) open pipe macrobubble aerator and the 6 × 0.5 mm (multiple holes) open pipe are included in this comparison.…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations